2018
DOI: 10.1186/s13148-018-0464-5
|View full text |Cite
|
Sign up to set email alerts
|

Altered DNA methylation is associated with aberrant gene expression in parenchymal but not airway fibroblasts isolated from individuals with COPD

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is a heterogeneous disease of the lungs that is currently the fourth leading cause of death worldwide. Genetic factors account for only a small amount of COPD risk, but epigenetic mechanisms, including DNA methylation, have the potential to mediate the interactions between an individual’s genetics and environmental exposure. DNA methylation is highly cell type-specific, and individual cell type studies of DNA methylation in COPD are sparse. Fibroblasts are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…CNVs in the testis-speci c Y-encoded protein (TSPY) gene have been linked to prostate cancer and human male infertility [23][24][25]. CNVs in the stem cell factor receptor (KIT) gene are linked to porcine white coat color [26], while CNVs in the agouti signaling protein (ASIP) gene in uences coat color of goat breeds [27]. We detected in the present study CNVs in BOC2, the copy number in the Qingjiao Ma (white skin chicken) being almost 2-fold larger than in the Guangxi Huang (yellow skin chicken) breed, suggesting that a lower CNV may lead to down-regulation of BCO2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…CNVs in the testis-speci c Y-encoded protein (TSPY) gene have been linked to prostate cancer and human male infertility [23][24][25]. CNVs in the stem cell factor receptor (KIT) gene are linked to porcine white coat color [26], while CNVs in the agouti signaling protein (ASIP) gene in uences coat color of goat breeds [27]. We detected in the present study CNVs in BOC2, the copy number in the Qingjiao Ma (white skin chicken) being almost 2-fold larger than in the Guangxi Huang (yellow skin chicken) breed, suggesting that a lower CNV may lead to down-regulation of BCO2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…DNAm has a high level of cell-type specificity, there are some studies on DNAm of individual cell types in patients with COPD. Clifford et al (2018) had studied the genomic DNAm of fibroblasts isolated from lung parenchyma and airway, and found DNAm to be related to differential gene expression only in the parenchymal fibroblasts. In addition, 359 individual differential CpG loci were found in the parenchymal fibroblasts.…”
Section: Biomarker In Tracheal Epithelium and Lung Tissuementioning
confidence: 99%
“…In addition, 359 individual differential CpG loci were found in the parenchymal fibroblasts. The methylation sites of OAT and GRIK2 genes significantly increased their expression in COPD cells ( Clifford et al, 2018 ). Barnawi et al (2017) had found phagocytosis of apoptotic cells by alveolar macrophages in patients with COPD to be controlled by epigenetic regulation, and decrease of methylation to possibly be the cause of increased S1PR5 gene expression in alveolar macrophages and of the defect in COPD-related efferent cells.…”
Section: Biomarker In Tracheal Epithelium and Lung Tissuementioning
confidence: 99%
“…Genome‐wide DNA methylation profiles and gene expression analyses in parenchymal cells, small airways and lung tissue suggest that aberrant DNA methylation patterns occur in numerous genes linked to functions and pathways important to COPD (Clifford et al, ; Morrow et al, ; Vucic et al, ). In a study examining homogenized lung tissue samples from patients with COPD, the top differentially methylated sites included cholinergic receptor muscarinic 1 (M 1 ), which is related to the PI3K‐Akt signalling pathway and bronchoconstriction of the airways, as well as glycosyltransferase 1 domain containing 1 ( GLT1D1 ) and deltex E3 ubiquitin ligase 1 ( DTX1 ), implicated respectively in reduced responses to LT modifiers in the treatment of asthma and in the development of natural killer T cells through regulating Notch signalling (Morrow et al, ).…”
Section: Dna Methylation Alterations In Chronic Diseasementioning
confidence: 99%
“…Genome-wide DNA methylation profiles and gene expression analyses in parenchymal cells, small airways and lung tissue suggest that aberrant DNA methylation patterns occur in numerous genes linked to functions and pathways important to COPD (Clifford et al, 2018;Morrow et al, 2018;Vucic et al, 2014). In a study examining F I G U R E 3 DNA methylation and demethylation occur through passive and active mechanisms.…”
Section: Copd and Dna Methylationmentioning
confidence: 99%